Comparison of Different Dosimetric Indices for Volumetric Arc Modulated Treatment Planning Using Two Different Treatment Planning Systems: A Feasibility Study for Total Body Irradiation - Kumari, Reena; Yadav, Budhi Singh; Kumar, Pankaj (Asian Pacific Journal of Cancer Care, 2023)
Objective: To compare two different treatment planning systems (TPSs) for plan quality and to assess the feasibility of volumetric modulated arc therapy (VMAT) for total body irradiation (TBI) on the Elekta Versa HD linear accelerator. Materials and Methods: Ten clinical VMAT TBI plans were replanned in Monaco TPS version 5 for retrospective dosimetric analysis and to evaluate the feasibility of treatment delivery on the Elekta Versa HD. A dose of 12 Gy in six fractions was prescribed to cover 95% of the planning target volume (PTV). Organs at risk (OARs) included the lungs, kidneys, heart, liver, and brain. Dosimetric optimization and calculations were performed in Monaco TPS with a statistical uncertainty of 1% and a 2 mm grid. Plan quality was assessed based on dosimetric indices such as conformity and homogeneity index, as well as OAR doses. Comparisons of optimization time, monitor units, and beam-on time were also analyzed. Pre-treatment verification was conducted using an Octavius phantom, and gamma analysis was performed using Low’s method with a dose difference of 3% and a distance to agreement of 3 mm criteria. The dosimetry of two VMAT TBI plans was compared using the Wilcoxon signed-rank test. Result: The calculated average maximum and mean doses to the PTV were 14.3321 Gy and 12.235 Gy for Eclipse, and 14.428 Gy and 12.198 Gy for the Monaco system, respectively. Planning time in Monaco was approximately 4.5-6 hours compared to 14-18 hours for Eclipse TPS. Statistically significant differences were observed between the results of the two TPSs in terms of monitor units, mean doses to the lungs, kidneys, heart, and liver, and planning time (P < 0.05). However, calculated p-values for homogeneity index (HI), conformity index (CI), and brain dose for both VMAT TBI plans were not statistically different. Conclusion: This study demonstrated the feasibility of VMAT TBI for the VERSA HD, offering faster and better optimization for a single target compared to Eclipse.